Autologous Hematopoietic Stem Cell Transplantation for Multiple Sclerosis, the Ottawa Protocol. Issue 5 (20th May 2022) - Puyade, Mathieu; Brunet, Francis; Carolina, Rush; Fergusson, Nathan; Makedonov, Ilia; Freedman, Mark S.; Atkins, Harold
Abstract: Autologous hematopoietic stem cell transplantation (aHSCT) is increasingly used to treat patients with highly active multiple sclerosis (MS) refractory to disease‐modifying therapy. Briefly, cyclophosphamide and filgrastim are used to mobilize autologous hematopoietic stem cells (HSC) into the circulation. HSC are harvested by leukapheresis, purified using a CD34 immunomagnetic selection process, and cryopreserved. Busulphan, cyclophosphamide, and rabbit anti‐thymocyte globulin are used to destroy the patient's autoreactive immune system, followed by infusion of the previously collected HSC, which reconstitute a naïve and self‐tolerant immune system. Many MS patients experience durable remissions with no evidence of new disease activity following aHSCT. Treatment‐related toxicity is rare, but potentially life‐threatening complications necessitate appropriate patient selection by MS neurologists and HSCT physicians. AHSCT must be performed with a highly trained multidisciplinary team expert to minimize morbidity and mortality. We present the current aHSCT procedure for an MS indication at The Ottawa Hospital, developed from our program's 20‐year experience. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Candidate selection Basic Protocol 2 : Autologous hematopoietic stem cell mobilization, collection, purification, and cryopreservation Basic Protocol 3 : Autologous hematopoietic stem cell transplantation Basic Protocol 4 : Supportive care following recovery from aHSCT (Beyond 100 days) Basic Protocol 5 : Ongoing evaluation of multiple sclerosis